Critiquing Modernist Approaches to the Qur’an: A Case Study of Mohammed Arkoun’s Hermeneutics - Tariq Amir Rayyan; Nurul Afiqah binti Ahmad; Dayang Siti Rahmah Haji Abdullah; Nurul Huda Zainal Abidin (Senarai: Journal of Islamic Heritage and Civilization, 2025)
The birth of modern thought in Islam, especially in the study of the Qur'an, was a critique of interpretation in the classical and middle ages, the interpretation at that time, according to him, was only coloured by the use of repeated history, political interests, etc., so that it was unable to produce the meaning of the text according to the needs of the times. Departing from this background, contemporary interpreters provide alternatives to reading the Qur'an that is scientific with the hermeneutic method, one of which is Mohammed Arkoun. This paper will describe Arkoun's thoughts on the hermeneutics of the Qur'an, which has attracted much controversy among Muslims and criticizes his thoughts. This type of qualitative research (library research) uses a descriptive-analytic approach. The study results show that Arkoun's hermeneutics has many shortcomings and aspects that must be abandoned. On a practical level, Arkoun's hermeneutics can only be used at the mahaulal Qur'an level, not at the ma fi Qur'an.